Acoustic Response of an Isotropic Beam Under Axially Variable Loads Using Ritz and Rayleigh Integral Methods - BALIREDDY, Somi Naidu; PITCHAIMANI, Jeyaraj; MAILAN CHINNAPANDI, Lenin Babu; CHINTAPALLI, V.S.N. Reddi (Archives of Acoustics, 2022)
Vibro-acoustic response of an isotropic beam under the action of variable axial loads (VALs), is presented in the study. Effects of six different types of VALs and three types of end conditions on buckling, free vibration and sound radiation characteristics are investigated. Static buckling and free vibration behaviours using shear and normal deformable theorem and Ritz method. However, the forced vibration response is evaluated using modal superposition method and the acoustic radiation characteristics are obtained using Rayleigh integral. The nature of variation of VALs and end conditions are influencing buckling and free vibration characteristics remarkably. Results indicate that the acoustic response is highly sensitive to the nature of VAL and intensity of the VAL. In general, sound power at resonance decreases when the magnitude of VAL is increased.